Perspektif Hukum dan HAM terhadap Eksistensi Aliran Keagamaan di Indonesia - -, Rohidin (Pandecta Research Law Journal, 2011)
Penelitian bertujuan untuk menganalisis eksistensi aliran keagamaan di Indonesia yang difatwa sesat oleh MUI, ditinjau dari perspektif Hukum dan HAM. Penelitian ini menggunakan dua jenis data yakni primer dan sekunder. Data primer dikumpulkan melaui wawancara dengan sejumlah informan dari MUI, Ahmadiyah, dan Ahli-ahli agama Islam. Hasil penelitian ini menunjukkan bahwa aliran-aliran keagamaan yang difatwa sesat oleh MUI tersebut, dalam perspektif MUI tidak dianggap sebagai kelompok agama yang resmi diakui oleh negara maupun menurut ajaran agama Islam yang sudah establish. Hal ini didasarkan pada ketentuan al-Qur’an dan Hadist, serta ketentuan hukum positif Indonesia. Kontroversi terhadap fatwa MUI ini dipicu oleh beberapa faktor. Pertama, adanya perbedaan antara pandangan MUI dengan para aktivis HAM dalam memaknai kebebasan beragama. MUI mendasarkan pandangannya pada norma-norma agama dan hukum positif, sementara para aktivis HAM mendasarkan pada norma-norma HAM Universal.This research attempt to analyze the existence of the religious sectes in Indonesia from perspective of the international human rights law. This research use the primary and secondary data. The primary data was collected through interview with the some informant such as MUI, Ahmadiyah, and Human rights activist. The result of this research show, that the existence of the religious sectes in Indonesian law system are normatively not be considered as a religious group. They are perceived by MUI as the religious deviate. In the normative paradigm MUI use it argument through some Al-Qur’an verses and also hadist in determining weather one religion group learned saying deviate or not. And the MUI positive paradigm is using its argument through some criminal law articel in determining one religion group deviate or not. Some factors which is made the fatwa controversion are there two causes. First, because of different perspective between MUI with democracy and human rights activist in viewing the case. MUI views that the case as religion shame, but the democracy and human rights views as a a religious liberty. And second is that MUI’s opinion of Indonesia system is religion state according to the first article of Pancasila. But according to the domocracy and human rights views that Indonesia system is a democracy state not a religion state. According to the human right law perspective, the fatwa is contradiction with the covenan of ICCPR. Because the covenan is guarantee the religion liberty.